CHLOROPHYL CONTENT IN LEAVES OF NON-TRADITIONAL OIL CROPS - Baxramova Nilufar Nazarovna; Khojamkulova Yulduzoy Jahonkulovna; Rustamova Shaxnozaxon Uktam kizi (Web of Journals Publishing, 2025)
This article studies the amount of chlorophyll grains in the leaves of non-traditional oilseed crops during the tillering phases of the growth period. The results of the analysis of the causes and consequences of changes in the amount of chlorophyll grains in the leaves during these periods are reflected.
Keywords: Oilseed radish, mustard, rape, tillering, chlorophyll meter, chlorophyll.